Campur Kode pada Iklan di Media Sosial Instagram @mariseruput - Sapna, Hassya Ancelia; Astuti, Sri Puji (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2025)
AbstractLanguage is one of arbitrary vowel symbol used in communication. In the use of language, there is often mixing between mother tongue and other languages or insertion of languages or code mixing. Code mixing can be found in various speech events, even in advertisements. Language can affect human behavior, advertisements use language to influence potential customers. As technology develops, now advertisements can also be found on social media Instagram. The purpose of this study is to explain the code mixing that exists on the social media Instagram @mariseruput. This type of research is qualitative research. The theory used is sociolinguistic theory. The method used is the documentation method with note-taking technique. The results of the research show that the form of code mixing is the insertion of words, baster, and phrases. Factors that cause code mixing to occur are the result of informal situations between speakers and speech partners, the speaker's inability to find equivalent words in the language being used, and there being no exact equivalent words in the language being used.Keywords: language, advertisement, code mixAbstrakBahasa adalah satu simbol vokal arbitrer yang digunakan dalam komunikasi. Dalam penggunaan bahasa, sering terjadi percampuran antara bahasa ibu dengan bahasa lain atau penyisipan bahasa atau campur kode. Campur kode dapat ditemui di berbagai peristiwa tutur bahkan pada iklan. Iklan menggunakan bahasa untuk mempengaruhi calon konsumennya. Seiring berkembangnya teknologi, kini iklan dapat ditemui juga pada media sosial Instagram. Tujuan penelitian ini adalah menjelaskan campur kode yang ada pada iklan di media sosial Instagram @mariseruput. Jenis penelitian ini adalah penelitian kualitatif. Teori yang digunakan adalah teori sosiolinguistik. Metode yang digunakan adalah metode dokumentasi dengan teknik simak catat. Hasil penelitian menunjukan bentuk campur kode berupa penyisipan kata, baster, dan frasa. Faktor yang menyebabkan terjadinya campur kode tersebut adalah akibat situasi informal antara penutur dan mitra tutur, ketidakmampuan penutur mencari padanan kata dalam bahasa yang sedang digunakan, tidak ada padanan kata yang tepat dalam bahasa yang sedang digunakan.Kata kunci: bahasa, iklan, campur kode